Physiological implications of partial defoliation of the grapevine (Vitis vinifera L. cv. Cabernet Sauvignon) - Hunter, Jacobus Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD) -- Stellenbosch University, 1991.